Internet of Things: Data Acquisition of Rich-Sensor Smart Phones - Olufowobi, Lawal (My University, 2015)
The Internet of Things is the next step in connectivity in which not just humans are connected to devices, but everyday devices and objects are equipped with some sensors and circuitry and are able to communicate with each other. A smart phone is a typical device that shows the potential of the Internet of Things as they are already quite ubiquitous and have impacted billions of people around the globe. Ranging from healthcare, education, entertainment and agriculture, the use of IoT devices, particularly smart phones has permeated our daily routine in life and the rate of growth is not slowing down. Wapice Ltd has released an IoT platform, IoT-Ticket, which provides a platform to connect any devices to the Internet of Things and provide real-time analysis, monitoring and reports for consumers and industrial usage. In this work, state-of-the art IoT will be explored and a cross-platform API for the IoT-Ticket platform which can be used to send and receive device’s data in a simple, secure and intuitive way will be created. Beyond this, a study application that makes use of artificial neural networks using sensor data from a mobile device via the API will also be developed.
Keywords: IoT; smart phones; REST API; neural networks; OBD2; fi=Communications and System Engineering|en=Communications and System Engineering|; fi=Communications and System Engineering|en=Communications and System Engineering|